Malignant transformation of glucagonoma with SPECT/CT In-111 OctreoScan features: A case report. Issue 50 (December 2017) - Corrias, Giuseppe; Horvat, Natally; Monti, Serena; Basturk, Olca; Lin, Oscar; Saba, Luca; Bodei, Lisa; Reidy, Diane L.; Mannelli, Lorenzo
Abstract: Rationale: Glucagonoma is an uncommon disease but it has been associated with a pattern of symptoms defined as glucagonoma syndrome. These symptoms, if promptly recognized, could help to speed up the diagnosing process. Patient concerns: We report a case of a 68-year-old woman with a pancreatic glucagonoma. Her symptoms at the onset were typical of the glucagonoma syndrome. Diagnoses: After a significant weight loss, she underwent a computer tomography scan of the abdomen, which showed a hypervascular lesion of the tail of the pancreas and hypervascular lesions of the liver. An ultrasound guided biopsy was performed and pathology was consistent with glucagonoma. Her blood glucagon levels were elevated. Outcomes: She was treated with chemotherapy and somatostatin analogs. After 4 years, the disease had a malignant transformation, and metastases suddenly started to grow up. She stopped being responsive to treatment and eventually passed away. Lessons: Due to its rarity, clinical diagnosis is challenging and generally it comes after a long interval since the onset of symptoms. Awareness of physicians and dermatologists of the characteristic necrolytic migratory erythema, and of the other symptoms, often leads to early diagnosis.